It Takes a Village: an Empirical Analysis of How Husbands, Mothers-in-law, Health Workers and Mothers Influence Breastfeeding Practices in Uttar Pradesh, India (P10-149-19). (13th June 2019) - Young, Melissa Fox; Nguyen, Phuong; Kachwaha, Shivani; Tran, Lan; Ghosh, Sebanti; Agrawal, Rajeev; Escobar-Alegria, Jessica; Menon, Purnima; Avula, Rasmi
Abstract: Objectives: Evidence on strategies to improve infant and young child feeding in India, a country that carries the world's largest burden of undernutrition, is limited. In the context of a program evaluation in two districts in Uttar Pradesh, we sought to understand the multiple influences on breastfeeding practices and to model potential program influence on improving breastfeeding. Methods: A cross-sectional survey was conducted among 1838 recently delivered women, 1194 husbands and 1353 mothers/mothers-in-law (MMIL) in Uttar Pradesh, India. We used bivariate and multivariate logistic regression models to examine the association between key determinants (maternal, household, community and health services) and breastfeeding outcomes (early initiation of breastfeeding (EIBF), pre-lacteal feed and exclusive breastfeeding (EBF). We used population attributable risk analysis to estimate potential improvement in breastfeeding practices. Results: Breastfeeding practices were suboptimal: Low EIBF (26.3%) and EBF (54%) but high pre-lacteal feeding (33%). EIBF was positively associated with maternal knowledge, counseling during pregnancy/delivery, and vaginal delivery at a health facility. Pre-lacteal feeds were less likely to be given to infants when the mothers had higher knowledge, beliefs and self-efficacy, and delivered at a health facility and MMIL had attended school. EBF was positively associated with maternal knowledge, beliefs and self-efficacy, parity and socio-economic status. High maternal stress and domestic violence contributed to lower EBF. Under optimal program implementation, we estimate EIBF can be improved by 25%, pre-lacteal feeding can be reduced by 25% and EBF can be increased by 23%. Conclusions: A multifactorial approach, including maternal, health service, family and community-level interventions has the potential to lead to significant improvements in breastfeeding practices in Uttar Pradesh. Funding Sources: The Bill & Melinda Gates Foundation, through Alive & Thrive, managed by FHI 360.